Burden of Sickle Cell Disease in Ghana: The Korle-Bu Experience - Eugenia V. Asare; Ivor Wilson; Amma A. Benneh-Akwasi Kuma; Yvonne Dei-Adomakoh; Fredericka Sey; Edeghonghon Olayemi (Advances in Hematology)
In Africa, sickle cell disease (SCD) is a major public health problem with over 200,000 babies born per year. In Ghana, approximately 15,000 (2%) of Ghanaian newborns are diagnosed with SCD annually. A retrospective review of medical records of all SCD patients aged 13 years and above, who presented to the sickle cell clinic at Ghana Institute of Clinical Genetics (GICG), Korle-Bu, from 1st January 2013 to 31st December 2014, was carried out, using a data abstraction instrument to document their phenotypes, demographics, attendance/clinic visits, pattern of attendance, and common complications seen. During the period under review 5,451 patients were seen at the GICG, with 20,788 clinic visits. The phenotypes were HbSS (55.7%) and HbSC (39.6%) with other sickle cell phenotypes (4.7%). Out of the 20,788 clinic visits, outpatient visits were 15,802 (76%), and urgent care visits were 4,986 (24%), out of which 128 (2.6%) patients were admitted to the Teaching Hospital for further management of their acute complications. There were 904 patient referrals (out of 5,451 patients) for specialist care; the 3 specialties that had the most referrals were Obstetrics and Gynaecology (168 patients), Orthopaedics (150 patients), and Ophthalmology (143 patients). In 2014, complications seen at KBTH included 53 patients with avascular necrosis (AVN) and 61 patients with chronic leg ulcers. Our centre has a large number of patients living with sickle cell disease. From our experience, early recognition and referral of sickle cell related complications can reduce morbidity and mortality associated with this disease. A multidisciplinary approach to care of SCD patients is therefore important.